THE OPTIMIZATION STRATEGY OF DEFENSE DIPLOMACY IN THE STRATEGIC DIALOGUE FORUM: INDONESIA'S PARTICIPATION IN THE SHANGRI-LA DIALOGUE - Jonni Mahroza; Anak Agung Banyu Perwita; Frega Ferdinand Wenas Inkiriwang (Jurnal Dinamika Global, 2024)
This study discusses Indonesia’s Defense Diplomacy optimization strategy in the Shangri-La Dialogue forum. It also deciphers the role of the Indonesian Minister of Defense in achieving national interests in the strategic forum. The findings show that the formulation of Indonesia's national interest in defense diplomacy refer to the Preamble to the 1945 Constitution, the application of free and active foreign policy, and the vision of the President. The role of Defense Minister is very vital in articulating Indonesia's national interests through effective speeches in the strategic dialogue forums. This article shows that despite the challenges due to dynamics in the scope of global and regional geopolitics, the involvement of the Indonesian Defense Minister in strategic forums has succeeded in strengthening Indonesia's diplomacy to the international arena and provides positive contributions to regional stability. This study recommends the need to develop more structured defense diplomacy strategy and long-term vision to face growing global challenges.